Fishing of Tatars of the Irtysh Forest-Steppe Region in the 19th — Early 21st Centuries - M. N. Tikhomirova; K. N. Tikhomirov (Научный диалог)
The issues of fishing among the West Siberian Tatars living on the territory of the Omsk region in the forest-steppe zone on the left bank of the Irtysh River are considered. The authors dwell on the characteristics of the traditional aquatic areas of the XIX — early XXI century, fishing objects, tools and methods of fishing. It is proved that the fishing of the Tatars in these settlements was an auxiliary branch of the economy in the past and present. It was shown that they fished almost all year round, mainly on lakes, where the main object of fishing was crucian carp. It is concluded that fishing was more developed among residents of settlements in the area of the village of Yalankul. It is shown that the Tatars of the villages in the area of the Ulenkul village are now less engaged in it because of the drying up of water bodies, as well as because of the withdrawal of lakes from nature management for transfer to the hunting farm and the reserve. The novelty of the research is seen in filling the gaps in the study of this topic. The authors note that material was collected about the fishing of the population, which previously consisted mainly of Siberian Bukharians and was actually assimilated by the Tatars.